Vaccine‐induced immune thrombotic thrombocytopenia with ChAdOx1 nCoV‐19 is rare in Asia. Issue 1 (15th January 2022) - Boonyawat, Kochawan; Angchaisuksiri, Pantep
Abstract: Background: Vaccination with ChAdOx1 n‐CoV‐19 is associated with a rare syndrome called vaccine‐induced immune thrombotic thrombocytopenia (VITT). VITT has been reported mainly in Western countries, whereas the report of VITT in Asians is sparse. Objectives: To report a case series of VITT following ChAdOx1 n‐CoV‐19 in Thailand and to estimate the incidence of VITT among Asian countries. Methods: We retrieved the number of VITT patients and the total inoculation doses from the database of the Thai Ministry of Public Health. We performed a literature search including published articles and gray literature to estimate the incidence of VITT. The incidences of VITT by countries and respective confidence intervals were calculated. Results: By the end of August 2021, five VITT cases occurred after 15 million doses of ChAdOx1 n‐CoV‐19 in Thailand. The median age was 31 years, and 60% were women. The incidence of VITT is estimated at 1 in 3 million. In other Asian countries, only a few cases of VITT have been reported. The incidence of VITT is much lower than in those of Western countries, which is estimated at 1 in 100, 000. The fatality rate was 44% in this study. Conclusions: Although the incidence of VITT in Asians is low, the mortality rate is substantially higher. We urge that public awareness of this syndrome be raised, as early recognition and appropriate treatment of this syndrome following ChAdOx1 n‐CoV‐19 are crucial to improve the outcome.